2013
DOI: 10.1186/1748-7188-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Inferring species trees from incongruent multi-copy gene trees using the Robinson-Foulds distance

Abstract: BackgroundConstructing species trees from multi-copy gene trees remains a challenging problem in phylogenetics. One difficulty is that the underlying genes can be incongruent due to evolutionary processes such as gene duplication and loss, deep coalescence, or lateral gene transfer. Gene tree estimation errors may further exacerbate the difficulties of species tree estimation.ResultsWe present a new approach for inferring species trees from incongruent multi-copy gene trees that is based on a generalization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…The tick species tree was inferred using the MulRF software package, which is a tree that minimizes the modified RobinsonFoulds (RF) distance for all input gene trees (CHAUDHARY et al, 2013(CHAUDHARY et al, , 2015. MulRF infers species trees from multi-copy gene trees using a generalization of RF topological distance, and it works by minimizing the total RF distance from the input multi-labeled trees, being relatively accurate in spite of evolutionary processes affecting single gene trees such as gene duplication and loss, deep coalescence, or lateral gene transfer (given our dataset, the most pervasive are gene duplication and loss).…”
Section: Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The tick species tree was inferred using the MulRF software package, which is a tree that minimizes the modified RobinsonFoulds (RF) distance for all input gene trees (CHAUDHARY et al, 2013(CHAUDHARY et al, , 2015. MulRF infers species trees from multi-copy gene trees using a generalization of RF topological distance, and it works by minimizing the total RF distance from the input multi-labeled trees, being relatively accurate in spite of evolutionary processes affecting single gene trees such as gene duplication and loss, deep coalescence, or lateral gene transfer (given our dataset, the most pervasive are gene duplication and loss).…”
Section: Phylogenymentioning
confidence: 99%
“…Its power lies in not assuming any specific evolutionary process during the analysis (i.e. incomplete lineage sorting, gene duplication and/or gene loss).The MulRF method produces more accurate species trees than other gene tree parsimony approaches (CHAUDHARY et al, 2013). Nevertheless, because it works like a consensus tree, no nodal supports are available, so this issue must be overcome beforehand; we did this by collapsing branches with less than 70% support in each gene tree using TreeCollapseCL4 (HODCROFT et al, 2014), as mentioned above.…”
Section: Phylogenymentioning
confidence: 99%
“…However, recently, Chaudhary et al (2013) demonstrated by simulation that the RF-based parsimony approach often outperforms the reconciliation methods that use the gene duplication or mutation costs. A recent study of Yang and Warnow (2011) also suggests that the duplication-cost-based approach has poorer performance at large.…”
Section: Resultsmentioning
confidence: 99%
“…The scoring models used in these methods include the duplication cost (that is, the number of duplications), the mutation cost (that is, the number of gene duplication and loss events), the deep coalescence cost (that is, the number of incomplete lineage sorting events), and the Robinson-Foulds (RF) distance (Bansal et al, 2010;Bayzid et al, 2012;Chang et al, 2013;Chaudhary et al, 2013;Than and Nakhleh, 2009;Wehe et al, 2008;Yu et al, 2011). Since finding the parsimony tree from gene trees is NP-hard for the reconciliation scoring models (Bryant, 1997;Ma et al, 2000;Zhang, 2011), existing methods all compute a species tree by navigating through the part of the species tree space guided by the reconciliation score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation